Treatment of Complicated Coronary Heart Disease after Successful Prehospital Resuscitation in a Public Place - M. L. Rudenko; N. O. Ioffe; V. V. Vayda; A. A. Pavlykova-Chertovska (Ukrainian Journal of Cardiovascular Surgery, 2021)
The current problem of modern medicine is the lack of public awareness about personal health, late diagnosis of diseases, untimely prehospital care and treatment of existing complications. This applies to all branches of medicine, especially cardiology and cardiac surgery. Coronary heart disease occupies one of the leading places in the structure of mortality due to cardiovascular diseases. This is mainly due to the fact that patients seek medical care with complicated forms of coronary heart disease like sudden cardiac death, cardiac arrhythmia (ventricular fibrillation, AV blockade, sinus bradycardia and tachycardia), formation of left ventricular (LV) aneurysm, LV free wall rupture and LV false aneurysm, mitral regurgitation. In such cases, all actions must be early, staged, well established, and concordant with clear algorithm.The aim. To demonstrate our clinical case as an example of proper logistics, rapid response and timely surgical treatment of complicated forms of coronary heart disease.Clinical case. Patient F., born in 1964, was admitted to the clinic on March 24, 2021 with a diagnosis of coronary heart disease: acute non-Q-wave myocardial infarction of the posterolateral LV since March 22, 2021. Clinical death with successful resuscitation at the prehospital stage (03/22/2021). Ventricular fibrillation (03/22/2021). Multivessel coronary artery disease. Mitral valve regurgitation grade II-III. Tricuspid valve regurgitation grade I-II. Pulmonary hypertension grade I. Hypertensive disease grade III, degree 3, risk 4 (very high). Heart failure II A with a moderately reduced LV ejection fraction (47%). NYHA3. Closed chest injury (03/22/2021): fracture of the ribs without displacement: ribs 4-8 on the left, ribs 4-8 on the right. He considers himself ill since March 22, 2021, when he suddenly felt severe pain in his chest and fell unconscious. According to witnesses, the man got out of the subway and fell unconscious, without breathing and pulse. Due to the presence of defibrillators at the subway station, successful resuscitation was conducted by police officers before the ambulance crew arrival. Clinical and instrumental studies were performed after hospitalization. The patient was taken to the operating room on 03/24/2021 at 5:30 PM, 50 minutes after admission to the National Amosov Institute, Kyiv. Urgent off-pump coronary artery bypass grafting of 3 coronary arteries was performed. A cardioverter-defibrillator was implanted due to the history of clinical death and the conclusion of daily ECG monitoring. The intra- and postoperative period was uneventful, the patient was discharged in satisfactory condition for rehabilitation.Conclusions. Our clinical experience shows that timely prehospital care, proper logistics and surgical correction of coronary heart disease not only saves but also significantly improves the quality of life of the patient in the future.